Beyond speeches and intentions, how to boost the regulatory and institutional framework to developrenewable energies in WAEMU? - (:unkn) unknown (My University, 2014)
This communication aims to demonstrate that the West African Economic and Monetary Union has all the assets to succeed in its energy transition, in the similar way as in its transition to mobile phones. It is about keeping the effort to capitalize on existing work, to coordinate public policies with research and action plans at Union level. The example of Morocco in terms of renewable energies and energy efficiency is presented.
Keywords: African Research